1997
DOI: 10.1038/sj.bjp.0701033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levcromakalim and nucleoside diphosphates on glibenclamide‐sensitive K+ channels in pig urethral myocytes

Abstract: 1 E ects of levcromakalim and nucleoside diphosphates (NDPs) on both membrane currents and unitary currents in pig proximal urethra were investigated by use of patch clamp techniques (conventional whole-cell con®guration, nystatin perforated patch, cell-attached con®guration and inside-out patches). 2 Levcromakalim produced a concentration-dependent outward current at a holding potential of 750 mV. The peak current amplitude showed little variation when measured by either conventional whole-cell or nystatin pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
42
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 35 publications
8
42
1
1
Order By: Relevance
“…The only other single studies that have been carried out were in the pig, in which an ATP-sensitive K ϩ current has been found (25)(26)(27). There is evidence that this current may contribute to the resting membrane conductance (27). However, because this current was neither voltage nor Ca 2ϩ sensitive, it is unlikely to play a part in determining the shape of the slow wave, which in any case has not been demonstrated in the pig (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only other single studies that have been carried out were in the pig, in which an ATP-sensitive K ϩ current has been found (25)(26)(27). There is evidence that this current may contribute to the resting membrane conductance (27). However, because this current was neither voltage nor Ca 2ϩ sensitive, it is unlikely to play a part in determining the shape of the slow wave, which in any case has not been demonstrated in the pig (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, because so far there have been no electrophysiological studies of the human urethra, the validity of different animal models remains to be established. The only other single studies that have been carried out were in the pig, in which an ATP-sensitive K ϩ current has been found (25)(26)(27). There is evidence that this current may contribute to the resting membrane conductance (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with previous studies, it has been shown that K ATP channels in pig urethra are activated by cromakalim and intracellular NDPs and inhibited by glibenclamide (Teramoto et al, 1997). On the other hand, K ATP channel properties in pig detrusor smooth muscle cells are poorly understood.…”
mentioning
confidence: 52%
“…Effect of Intracellular MgGDP and cAMP on the Levcromakalim-Induced Outward Current. In a wide variety of preparations, intracellular NDPs such as GDP, UDP, IDP, and ADP have been reported to augment K ATP channel activity (Kajioka et al, 1991;Beech et al, 1993;Kamouchi and Kitamura, 1994;Teramoto et al, 1997). In addition, protein kinase (PK)A and/or PKC have been reported to activate a levcromakalim-sensitive K ϩ channel, presumably K ATP (Standen et al, 1998).…”
Section: Resultsmentioning
confidence: 99%